Kinerja Campuran Beraspal Hangat Laston Lapis Pengikat (AC-BC) dengan Reclaimed Asphalt Pavement (RAP) - Indra Maha; Bambang Sugeng Subagio; Furqon Affendi; Harmein Rahman (Jurnal Teknik Sipil, 2015)
This paper presents the results of laboratory study of AC-BC asphalt mixture reusing reclaimed asphalt pavement (RAP) by warm mix method. 30% of RAP is combined with new aggregate in the mixture. Rejuvenating agent Cyclogen L was used to activate RAP asphalt binder. With 3% organic wax Sasobit, temperature of mixing and paving was set at 135°C and 123°C, 30°C lower than conventional hot mix asphalt (HMA) with unmodified asphalt binder 60/70 penetration. Three mixtures were set in this research, consisting of hot mix asphalt conventional mixture (identified as HM), warm mix asphalt mixture (identified as SASO) and warm mix asphalt with RAP (identified as SASORAP). Marshall design procedure was used to determine the optimum bitumen content (OBC). OBC for each mixture was 5,2%, 5,2% and 5,3% for HMA, SASO and SASORAP respectively. From Indirect Tensile Stress test result, all asphalt mixture meet moisture sensitvity requirement where Indirect Tensile Stress Ratio (ITSR) is higher than 80%. From resilient modulus and fatigue resistance test result, SASO and SASORAP showed a better performance than conventional mixture (HMA).